Полупроводниковые квантовые точки как источник генерации синглетного кислорода в фотодинамической терапии - Березовская, И. В.; Рожицкий, Н. Н. (ХНУРЭ, 2012)
Advances in nanotechnology can improve the photodynamic therapy method using semiconductor quantum-dimensional structure such as quantum dots. In this work modeling of photodynamic processes for singlet oxygen generation and its registration by chemical traps has been done. Obtained results show the quantum dots can be efficient photosensitizers in photodynamic therapy.
Keywords: наноэлектроника; полупроводниковые квантовые точки; фотодинамическая терапия